Adventitial adaptive immune cells are associated with ascending aortic dilatation in patients with a bicuspid aortic valve - Staal, Alexander H. J.; Cortenbach, Kimberley R. G.; Gorris, Mark A. J.; van der Woude, Lieke L.; Srinivas, Mangala; Heijmen, Robin H.; Geuzebroek, Guillaume S. C.; Grewal, Nimrat; Hebeda, Konnie M.; de Vries, I. Jolanda M.; DeRuiter, Marco C.; van Kimmenade, Roland R. J. (Frontiers in Cardiovascular Medicine, 2023)
Background Bicuspid aortic valve (BAV) is associated with ascending aorta aneurysms and dissections. Presently, genetic factors and pathological flow patterns are considered responsible for aneurysm formation in BAV while the exact role of inflammatory processes remains unknown. Methods In order to objectify inflammation, we employ a highly sensitive, quantitative immunohistochemistry approach. Whole slides of dissected, dilated and non-dilated ascending aortas from BAV patients were quantitatively analyzed. Results Dilated aortas show a 4-fold increase of lymphocytes and a 25-fold increase in B lymphocytes in the adventitia compared to non-dilated aortas. Tertiary lymphoid structures with B cell follicles and helper T cell expansion were identified in dilated and dissected aortas. Dilated aortas were associated with an increase in M1-like macrophages in the aorta media, in contrast the number of M2-like macrophages did not change significantly. Conclusion This study finds unexpected large numbers of immune cells in dilating aortas of BAV patients. These findings raise the question whether immune cells in BAV aortopathy are innocent bystanders or contribute to the deterioration of the aortic wall.